Real-time dosimetry with Yb-doped silica optical fibres. (28th April 2017) - Veronese, Ivan; Chiodini, Norberto; Cialdi, Simone; d'Ippolito, Eduardo; Fasoli, Mauro; Gallo, Salvatore; La Torre, Stefano; Mones, Eleonora; Vedda, Anna; Loi, Gianfranco
Abstract: Over the years, many efforts have been made to develop radiation detectors to handle the complex issues of small field dosimetry and achieve the increasing accuracy, precision and in vivo dose monitoring required by the new advanced treatment modalities. In this context, interest has surged in the development of sensors based on scintillating optical fibres. In this paper, the near-infrared radioluminescence and dosimetric properties of Yb-doped silica optical fibres, coupled with a laboratory prototype based on an avalanche photodiode, were studied by irradiating the fibres with photons and electron beams generated by a Varian Trilogy accelerator. The performance of the system in standard and small field sizes has also been investigated, comparing the output factor, percentage depth dose and off-axis ratio measurements of the prototypal detector with other commercial sensors, including the Exradin W1 scintillator. The results of this study demonstrate that the drawback due to the stem effect in Yb-doped silica optical fibres can be managed in a simple but effective way by optical filtering. The robustness of the system in complex dosimetric scenarios and the accuracy and precision achieved by Yb-doped fibres in relative dose assessments suggest an effective use of the system for real-time in vivo dosimetry applications.